Angiostensin-I converting enzyme (ACE) inhibitory activity of milk hydrolysate by enterococcus faecium DMF78 and its potential for a new milk-based beverage - Gonzales, Gerard Bryan L. (2009)
A study on the possibility of making a new milk-based beverage which would contain an anti-hypertensive promoting activity was done. Commercial sterile cow?s milk was used initially to simplify the variables since fresh pasteurized milk harbor a variety of microorganisms. enterococcus faecium DMF 78, a published local isolate, was used because several attempts to procure lactic acid bacteria reported from literature which exhibited high antihypertensive activity in sour milk was unsuccessful. Also, the attempt to buy ACE or Angiotensin Converting Enzyme from Sigma Chemicals at a very prohibitive cost for the monitoring experiments prompted us to try strategies to extract it fresh from porcine lung using this method. Thus, this study started first by exploring the local availability of the enzyme. Crude ACE was extracted from porcine lung obtained from the nearest slaughterhouse. The activity of this enzyme was confirmed using RP-HPLC method and was found to be 0.052 U/mL. this ACE extract was used in the subsequent screening of ACE inhibitory peptide found in milk hydrolysate by Enterococcus faecium DMF78. After 48 hours of incubation under optimal growth condition, the milk hydrolysate was able to inhibit ACE activity by 63%. IC50 value or the amount of protein in milk hydrolysate needed to inhibit 50% of ACE activity was found to be 0.88 mg/mL. the milk hydrolysate was then developed into two acceptable milk-based beverages. Consumer testing was performed to ascertain general acceptability of the products and to determine which of the two beverages was more preferred. The mean acceptability score of the sour milk drink and whey beverage was 7.94 and 7.09, respectively in a 9-point hedonic scale. Consumer perceptions on the products as well as the purchase intent of consumers were ascertained based on the consumers? answers on a questionnaire
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2009
Keywords: Angiostensin-I converting enzyme (ACE).; Hypertension; Milk; Sour milk; Milk-based beverages; Beverages; Milk hydrolysis; Genus enterococcus; Milk hydorlysate; Sour milk -- Products; Sour milk -- Beverages; Renin-angiostensin system (RAS).; Peptides; Hog lungs; Milk proteins